Infantile Galactosialidosis with Novel Mutation: An Early Presentation - Sharma, Sonia; Gupta, Shailesh; Mehta, A. P.; Sidana, Poonam (Journal of Pediatric Genetics, 2021)
Galactosialidosis (GS) is a rare lysosomal storage disorder. We reported here, the case of a 29-day-old boy who had increased body swelling, difficulty breathing, and petechiae on the trunk since birth. The antenatal history was unremarkable. Clinical laboratory findings included coarse facies, hepatosplenomegaly, gross ascites, thrombocytopenia, nephrotic range proteinuria, and bilateral hydronephrosis. The diagnostic challenge was resolved after genetic testing, which revealed GS with a novel homozygous c.1158dupA mutation.
Keywords: galactosialidosis; anasarca; thrombocytopenia; neonatal ascites; congenital nephrotic syndrome